2014
DOI: 10.1002/aoc.3120
|View full text |Cite
|
Sign up to set email alerts
|

The influence of triphenylantimony(V) catecholate and its spiroendoperoxide on lipid peroxidation

Abstract: The effects of triphenylantimony(V) catecholate Ph 3 Sb(Cat) (1) and its spiroendoperoxide Ph 3 Sb(L-O 2 ) (2) (Cat = 3,6-di-tert-butyl-4,5-dimethoxycatecholate) on lipid peroxidation (LP) in vitro and in vivo were examined in BALB/c line mice. A comparative study of the impact of compounds 1 and 2 on LP under similar conditions was made by measuring the formation of thiobarbituric acid reactive substances (TBARS). The anti-or pro-oxidant action of complexes 1 and 2 may be caused by the different redox level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We have previously shown that triarylantimony (V) complexes with catecholate ligands act as effective traps and can not only intercept molecular oxygen, but also neutralize alkylperoxy radicals and DPPH, promote the destruction of hydroperoxides, and inhibit lipid peroxidation processes [ 75 , 76 , 77 , 78 , 79 , 80 ]. In the continuation of our research, it was interesting to evaluate the effect of the RS group on the radical scavenging activity in the reaction with the stable DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that triarylantimony (V) complexes with catecholate ligands act as effective traps and can not only intercept molecular oxygen, but also neutralize alkylperoxy radicals and DPPH, promote the destruction of hydroperoxides, and inhibit lipid peroxidation processes [ 75 , 76 , 77 , 78 , 79 , 80 ]. In the continuation of our research, it was interesting to evaluate the effect of the RS group on the radical scavenging activity in the reaction with the stable DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the transition metals, the O 2 binding does not lead to a change in the antimony oxidation state, while the redox active ligand is involved in the redox reaction. The nature of functional groups in redox active ligands [ 65 , 66 , 67 , 68 ], as well as in substituents at a central antimony atom [ 69 , 70 , 71 , 72 , 73 , 74 ], affects the redox properties of antimony catecholates and their antioxidant activity [ 75 , 76 , 77 , 78 , 79 , 80 ]. Electron-donating groups in catecholate or at the antimony atom in complexes of the type CatSbR 3 shift the oxidation potential to the anodic region.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when carried out in air, this chemistry may also involve O 2 . Indeed, as demonstrated by Cherkasov et al, stiboranes resulting from the reaction of Ph 3 Sb with certain ortho -quinones may fixate O 2 to form semiquinone (SQ) peroxide adducts of type E , in which the O 2 2– unit bridges the antimony center and one of the carbon atoms of the ligand . One of the simplest examples of such a compound is E phenSQ/Ph , obtained by the reaction of Ph 3 Sb and 9,10-phenanthraquinone (phenQ) in air.…”
Section: Introductionmentioning
confidence: 99%
“…Triarylantimony(V) o-amidophenolates [ 47 , 48 ], as well as some triarylantimony(V) catecholates with electron-donor substituents [ 49 , 50 , 51 ], represent the first class of main group metal complexes, which can bind the molecular oxygen in a reversible manner. The related antimony(V) catecholates were found to be active in a radical scavenging [ 52 , 53 , 54 ], can be considered prospective inhibitors of oxidation processes, such as lipid peroxidation [ 55 , 56 ]. The modification of molecular structure and redox-properties of triorganylantimony(V) catecholates is possible via the use of different donor/acceptor substituents in a redox-active ligand [ 50 , 57 ], at organic groups bound to antimony [ 58 , 59 , 60 ], or coordination of a neutral or ionic ligand to the central antimony atom [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%